Respuestas

2012-04-22T21:48:22+02:00

5x+3(2x-3)=2

5x+6x-9=2

11x-9=2

11x=2+9

11x=11

x=11/11

x=1

2012-04-22T22:04:00+02:00

buenas tardes.5x+3(2x-3)=2
                      5x+6x-9=2
                      5x+6x=2+9
                      11x=11
                        x=11/11
                         x=1

 comprobacion:

                    5(1)+3(2( )-3)=2
                     5   + 6    -9=2

                        11-9=2
                          2=2                recuerda:toda ecuacion es una igualdad.saludos.